Case of organising pneumonia in HIV infection. Issue 11 (24th November 2022) - Yamauchi, Momoko; Kanie, Nobuhiro; Takahashi, Kensuke; Katoh, Shungo
Abstract : A man in his 50s presented to his doctor with a fever, sore throat, cough, dysgeusia and dyspnoea of several days' duration. Tests for HIV antigen, HIV antibody and HIV PCR were positive. He was referred to our hospital for initiation of antiretroviral therapy and bronchoscopy to clarify the cause of an abnormal lung shadow on chest CT. He was diagnosed with organising pneumonia, with concurrent HIV infection. His pulmonary lesions were remitted spontaneously, and he was administered a fixed-dose combination of tenofovir (50 mg), emtricitabine (200 mg) and bictegravir (25 mg) for HIV. This is a rare report of organising pneumonia with HIV infection. Physicians need to consider organising pneumonia when lung opacity is observed in a patient with HIV infection.